Detection and genome characterization of Middelburg virus strains isolated from CSF and whole blood samples of humans with neurological manifestations in South Africa. - Isabel Fourie; June Williams; Arshad Ismail; Petrus Jansen van Vuren; Anton Stoltz; Marietjie Venter (Public Library of Science (PLoS), 2022)
Background The Old world Alphavirus, Middelburg virus (MIDV), is not well known and although a few cases associated with animal illness have previously been described from Southern Africa, there has been no investigation into the association of the virus with human illness. The current study aimed to investigate possible association of MIDV infection with febrile or neurological manifestations in hospitalized or symptomatic patients fromGauteng, South Africa. Methods This study is a descriptive retrospective and prospective laboratory based study. Archived cerebrospinal fluid (CSF) samples submitted to the National Health Laboratory Service (NHLS), Tshwane Academic division for viral investigation from public sector hospitals in Gauteng as well as EDTA (ethylenediaminetetraacetic acid) whole blood samples from ad hoc cases of veterinary students, presenting with neurological and febrile illness, were selected and screened for the presence of alphaviruses using real-time reverse transcription(rtRT) PCR.Virus isolations from rtRT-PCR positive samples were conducted in Vero cell culture and used to obtain full genome sequences. Basic descriptive statistical analysis was conducted using EpiInfo. Results MIDV was detected by rtRT-PCR in 3/187 retrospective CSF specimens obtained from the NHLS from hospitalised patients in the Tshwane region of Gauteng and 1/2 EDTA samples submitted in the same year (2017) from ad hoc query arbovirus cases from veterinary students from the Faculty of Veterinary Science University of Pretoria.Full genome sequences were obtained for virus isolates from two cases; one from an EDTA whole blood sample (ad hoc case) and another from a CSF sample (NHLS sample).Two of the four Middelburg virus positive cases,for which clinical information was available, had other comorbidities or infections at the time of infection. Conclusion Detection of MIDV in CSF of patients with neurological manifestations suggests that the virus should be investigated as a human pathogen with the potential of causing or contributing to neurological signs in children and adults.